PERANAN UREA PADA PENGOMPOSAN SERBUK GERGAJI JEUNGJING (ALBIZIA FALCATARIA) - Ridwan Achmad Pasaribu (Jurnal Penelitian Hasil Hutan, 1989)
The  composting   experiment  for  the  manufacture   of  compost   from  jeungjing  sawdust  has been done  in the Forest Products  Research  and  Development    Centre,  Bogor.  The  study   reveals that  a combination   of 60 percent   of jeungjing  saw- dust  and  40 percent   of  rice straw  composted   for  about  35  days produced   compost   with  45,87   of  C/N ratio  which  is in- ferior compare  to the minimum   C/N ratio of  the soil that should  be less than 20.In  the past,   attempts  have  been  made   by  many   workers   to  reduce   C/N  ratio  of  compost.   Inclusion   of  additives such as urea in the composting,   has been successfully   done.The  composting   trials in the  Forest  Product  Research  and  Development    Centre  was prepared   by the mixture   of 60 percent   of jeungjing  sawdust  and 40 percent   of  rice straw,   on  which  an amount   of  O;   3;  3,5;   5,  7 percent  urea by weight was added  to the mixture.   The composting   time  were consecutively   8; 16; 24,  and 32 days.This experiment reveals that  :1.The  analysis  of  variance of  the  C/N ratio  content   of  the  compost  produced   by different   urea content   and composting time,  are significantly   different.2.The composition   of  60  percent   jeungjing  sawdust  and  40 percent   rice straw  composted   for  about  35  days,  produced compost   with  a  relatively   law  C/N  ratio  (about   18,46).    This  is  particularly   true  when   7,5   percent   of  the  urea was engaged  in the  composting   process.   The  C/N ratio content   has met  the requirement   of  the compost  for fertilizer  which is about  20.